Neurons in the Locus Coeruleus Modulate the Hedonic Effects of Sub-Anesthetic Dose of Propofol - Chen, Hui; Xu, Dan; Zhang, Yu; Yan, Yan; Liu, JunXiao; Liu, ChengXi; Shen, Wei; Yu, Tian; Liu, Jin (Frontiers in Neuroscience, 2021)
Propofol is a world wild used intravenous general anesthetic with ideal effects, but hedonic effects of propofol have been reported and cause addictive issue. There is little known about the neurobiological mechanism of hedonic effects of propofol. Increasing researches have shown that the dopaminergic nervous system of Ventral tegmental area (VTA) and the noradrenergic system of locus coeruleus (LC) play crucial role in hedonic experiences, which are putative sites for mediating the hedonic effects of propofol. In the present study, rat hedonic responses scale and place conditioning paradigm were employed to examine the euphoric effects of propofol. In vivo GCaMP-based (AVV-hSyn-GCaMP6s) fiber photometry calcium imaging was used to monitor the real-time neuronal activity in VTA and LC area in rats exhibiting propofol-induced euphoric behaviors. Then DREADDs (designer receptors exclusively activated by designer drugs) modulation using rAAV-hSyn-hM4D(Gi)-EGFP was performed to confirm the neuronal substrate that mediates the euphoric effects of propofol. The score of hedonic facial responses was significantly increased in 4 mg/kg group compare to 0 mg/kg group. The locomotor activity in the propofol-paired compartment was significantly increased at the 4 mg/kg dose compared to the saline-paired group. When compared to the 0 mg/kg group, the place preference increased in 4 mg/kg group. Administration of 4 mg / kg propofol trigger reliable increases in GcaMP fluorescence. However, in VTA GcaMP expressing rats, administration of 4 mg / kg propofol did not induce any change of GcaMP signals. The facial score and the place preference increased by 4 mg/kg propofol were abolished by chemogenetic inhibition of the neuronal activity in the LC area. Our results suggest that LC noradrenergic neurons, not VTA dopaminergic neurons, are directly involved in the hedonic effects of sub-anesthetic dose of propofol.